Stearic acid induces CCK and GLP-1 upregulation via GPR120/PLC-β, leading to reduced appetite in Hu sheep fed with rice straw - Chen, Xi; Nie, Xintian; Wang, Huanhuan; Yan, Shuping; Zhang, Yuanshu (Frontiers in Veterinary Science, 2022)
Due to the poor palatability of straw, feeding ruminants with straw alone reduces their feed intake, feeding untreated rice straw reduces ruminant feed intake, thus affecting the production efficiency of animal husbandry. However, the detailed mechanism by which straw affects ruminants’ feed intake is unclear. Therefore, this study aimed to elucidate the molecular mechanism by which a rice straw (RS)-based diet affects appetite regulation in Hu sheep. We found that RS promoted the secretion of CCK and GLP-1 and decreased feed intake. Blood metabolomics showed that RS activated the arachidonic acid metabolism, biosynthesis of unsaturated fatty acids, linoleic acid metabolism, and alpha-linolenic acid metabolism pathways, and the secretion of stearic acid (SA), their metabolic end product, increased significantly. GPR120, one of the classical receptors of long-chain fatty acids (LCFAs), can be involved in appetite regulation. However, the role of SA in satiety hormone regulation mediated by GPR120 in ruminants is unclear. In this study, in vivo experiments showed that in sheep fed with RS, SA increased significantly and activated GPR120/Ca2+, increasing the secretion of the satiety hormones CCK and GLP-1. In vitro mechanism studies showed that SA promotes GLP-1 and CCK secretion by activating GPR120-mediated downstream PKC and IP3R signaling pathways of PLCβ.